Gondang di Komunitas Parmalim Batak Toba: Teks, Konteks, dan Aspek Performatif - Irwansyah Harahap (Antropologi Indonesia, 2012)
This writing is about Gondang music which exists among the Toba Batak Parmalim community of Hutatinggi in the district area of Toba Samosir, North Sumatra province of Indonesia. Content of discussion includes an historical background of the people and knowledge and expressions of Gondang music among Toba Batak people in general and Parmalim community in particular. The performance aspects of Parmalim gondangs, including music ensembles, repertoires and ritual-musical practices, will also be discussed as part of discussion. key words: Teks, Kontekstualisasi, Performatif, Kebudayaan, Ekspresi Makna